MENINGKATKAN KEMAMPUAN KOMUNIKASI MELALUI MEDIA KARTU GAMBAR BERSERI BAGI ANAK AUTIS - Benazir -; Markis Yunus; Kasiyati - (Universitas Negeri Padang, 2013)
Abstract This study originated from the observation that researchers found when carrying out observations. Investigators found a child with autism who experience barriers in communication. Of observational studies found children are not able to communicate to convey his wish to ask something of objects. This study aims to improve children's ability to communicate through the good and the true the medium of drawing cards glow. This research uses experimental approach in the form of Single Subject Research (SSR), using the AB design. Subjects in this study were children with autism. Target Behavior in this study is the ability of the child in accordance with the communication criteria is good and right. Assessment is given observation. This research was first seen from the baseline or initial child ability in communication, after it resumed in the intervention condition. The data obtained were processed with graphics, so the results of this study can be clearly defined. Results of this study indicate that the ability of autistic children despite gradual increases in communication. In the baseline condition (A) the first day to the fifth day the child's ability horizontally ie 40%. In the intervention condition (B) increased from 40% to 80%. Child can do it gradually though the child is less than perfect. Thus the hypothesis is accepted with a tendency towards the positive, the stability trend variable and overlap virgin 0.3%, that is to say through the medium of drawing cards glow can improve communication skill autistic children in special schools Padang Harapan Bunda. Recommended to teachers to use radiant picture card media to improve communication skills for children with autism. Kata Kunci: Kemampuan Berkomunikasi, Kartu Gambar Berseri, Autis